The State's Efforts in Preserving the Environment Through Regulation - Devid Frastiawan Amir Sup (Sustainability (STPP) Theory, Practice and Policy, 2021)
Environmental Impact Assessment (EIA) must be owned by every business and/or activity that has an important impact on the environment. The EIA study covers various aspects and the results are very well used as material for making decisions on the feasibility of a business plan and/or activity. By including EIA in the planning process of a business and/or activity, a broader and deeper view will be obtained (so that optimal decisions can be made from the various available alternatives), as well as to consider the possible consequences in order to prepare steps to overcome negative impacts. and develop possible positive impacts. This study aims to describe regulations in Indonesia related to EIA. The method used is qualitative-descriptive-library. The results obtained are that there are several regulations regarding environmental conservation in Indonesia, namely Law No. 32/2009 concerning Environmental Protection and Management, PP No. 27/2012 concerning Environmental Permits, Permen LH No. 8/2006 concerning Guidelines for the Preparation of the EIA, and Permen LH No. 5/2012 concerning Types of Business and/or Activities Plans Required to Have an EIA.